2007
DOI: 10.1007/s00246-007-9037-7
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Relationship Between B-type Natriuretic Peptide and Pulmonary Vascular Resistance in Patients with Ventricular Septal Defect and Concomitant Severe Pulmonary Hypertension

Abstract: B-type natriuretic peptide (BNP) reflects volume overload on left ventricle and pulmonary hypertension (PH) in patients with ventricular septal defect (VSD). Pulmonary vascular resistance (PVR) has been reported to correlate positively with BNP in VSD patients with various degrees of PH. We aimed to investigate the relationship between PVR and BNP in VSD patients with severe PH. We examined 24 subjects with VSD concomitant severe PH aged from 2 months to 17 years (median: 4 months). The ratio of pulmonary to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…16 Ventricular septal defect A total of 11 articles concerning patients with ventricular septal defect were included, describing a total of 328 patients with unrepaired ventricular septal defect and 43 with repaired ventricular septal defect. 5,11,17,[21][22][23][24][25][26][27][28] All studies comprised children with mean/median age ranging from 4 months to 13.3 years, whereas no studies in adult patients were found. None of the studies reported separate results for muscular or (peri)membranous ventricular septal defect.…”
Section: Atrial Septal Defectmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Ventricular septal defect A total of 11 articles concerning patients with ventricular septal defect were included, describing a total of 328 patients with unrepaired ventricular septal defect and 43 with repaired ventricular septal defect. 5,11,17,[21][22][23][24][25][26][27][28] All studies comprised children with mean/median age ranging from 4 months to 13.3 years, whereas no studies in adult patients were found. None of the studies reported separate results for muscular or (peri)membranous ventricular septal defect.…”
Section: Atrial Septal Defectmentioning
confidence: 99%
“…Correlations between age and brain natriuretic peptide levels differed widely from non-significant to highly significant negative correlations. 21,24,27 Patients with clinical signs of cardiac failure revealed higher brain natriuretic peptide values than those without clinical signs. 26,28 In all, eight articles described correlations between brain natriuretic peptide and cardiac function parameters (Table 2).…”
Section: Atrial Septal Defectmentioning
confidence: 99%
“…Plasma BNP is also increased significantly in patients with left-to-right shunts, aortic valve stenosis, coarctation of aorta and patients with functionally univentricular heart in comparison with healthy subjects [31]. In patients with left-to-right shunt lesions, plasma BNP positively correlate to shunt volume, systolic RV pressure, mean pulmonary artery pressure and increasing pulmonary vascular resistance [31,32]. Plasma BNP 20 pg/ml and ANP of 50 pg/ml can identify children with mean pulmonary artery pressure of 20 mmHg with a sensitivity of 82% and 97%, respectively, and a specificity of 89% and 84%, respectively [32].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…In patients with left-to-right shunt lesions, plasma BNP positively correlate to shunt volume, systolic RV pressure, mean pulmonary artery pressure and increasing pulmonary vascular resistance [31,32]. Plasma BNP 20 pg/ml and ANP of 50 pg/ml can identify children with mean pulmonary artery pressure of 20 mmHg with a sensitivity of 82% and 97%, respectively, and a specificity of 89% and 84%, respectively [32]. No significant elevation of BNP is found in patients with pulmonary valve stenosis, tetralogy of Fallot, in patients missing a pulmonary ventricle with isolated cavopulmonary failure [31].…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…However, the relationship between NT-proBNP and catheterization findings was not studied. The only study in children was performed by Toyono et al (19); they investigated the role of NT-proBNP in 29 patients with VSD and severe PHT. Only four patients showed apparent Eisenmenger physiology.…”
Section: Discussionmentioning
confidence: 99%